Zoomorphic Images and Ornaments with Rosettes in Christian Art of the Caucasus: Formation Paths of the Traditional Schemes - Ekaterina Yu. Endoltseva (Anastasis: Research in Medieval Culture and Art, 2020)
The article deals with the pathes of the formation of the traditional schemes in Christian art of Caucasus. On the example of several motifs, some zoomorphic images and ornaments with rosettes, one can notice that their origins, which are found both in the Christian context and in everyday culture, could be associated with the stable influence of religious beliefs and cults dating back to the Neolithic era. Other images may have been inherited from an earlier local archaeological culture (Koban-Colchis).